Hysterosapingographic Evaluation Of Primary And Secondary Infertility - Prof. Nadia G.; Dr. Amal Ibrahim; Sumayyah Yousuf Mohammed (Aljameai, 2022)
Abstract : Infertility is a unique medical condition because it involves a couple rather than a single individual. Both the prevalence of infertility and the number of patients seeking the treatment of this disorder are increasing and especially in the third world. Approximately 8% of couples (52-80 million patients) worldwide are suffering from infertility. Although it is not a physically debilitating disease, infertility may severely affect the couple’s psychological harmony, sexual life and social function.Hysterosalpingography  (HSG): is an imaging modality used in assessing the fallopian tubes of patients with infertility. There have been reports suggesting that tubal pathologies may be responsible for most cases of secondary infertility.Result:The study showed that most of the patients had 2ry infertility (55%). The percentage of patients who had 1ry infertility was 45%.most of the patients with 1ry and 2ry infertility were between 20 and 40 years (86.7% 1ry and 90.9 2ry). the majority of patients with 1ry infertility (97.8%) had negative abortion history while 40% of the patients with 2ry infertility had negative abortion history. The majority of the patients with 2ry infertility (60%) had positive abortion history The cause of infertility in the current study was mainly due to both sexes (68.9% of 1ry infertility and 52.7% of 2ry infertility). About 95% of 1ry cases had no history compared with 49.1% of 2ry cases. Regarding the HSG result, the current study showed that abnormal cervix was higher in 2ry infertility than in 1ry infertility while abnormal uterus was higher in 1ry infertility than in 2ry infertility. The result showed that more abnormal Rt fallopian tube abnormalities was seen in 1ry than 2ry infertility patients. The result also revealed that abnormal Lt fallopian tube was more in 2ry infertility patients than the 1ry infertility patients.Conclusion The study concluded that secondary infertility is more common than the primary infertility. Tubal abnormalities also is more common in secondary infertility than primary infertility and most common tubal abnormality is two tubal block.الملخص:تشوهات الانبوب في العقم الاولي والثانوي أن العقم حالة طبية فريدة من نوعها لانها تشمل زوجين 8% من الازواج  في انحاء العالم يعانون من العقم حيث انه يؤثر بشدة علي الانسجام النفسي والحياة الجنسية والوظيفة الاجتماعية للزوجين وتعتبر (HSG)هي طريقة تصوير الرحم بالصبغة تستخدم في تقيم قناتي فالوب لمرضي العقم، وتهدف الدراسة  إلي تقيم التشوهات لقناتي فالوب التي تظهر في النساء اللتي تم فحصهن بواسطة HSG .المواد والطرق : كانت الدراسة بأثر رجعي قائمة علي  ( استبيان دراسة المقطع الرحمي ) تم اجراءوه  في عيادة  المختار والمسرة  الخاصة في  طرابلس –  ليبيا  خلال عام 2015 - 2016   تم اختيار 120 مريضة لديهم عقم تم تقسيم المرضي الي مجموعتين حسب نوع العقم اي مجموعة عقم اولي وعقم ثانوي خضع جميع المرضي لأختبار  HSG وتم الحصول علي البيانات التالية من المرضي :العمر , تاريخ التكافؤ , تاريخ الاجهاض , الحمل خارج الرحم , نوع العقم , سبب العقم , جراحات الحوض السابقة , تاريخ المرض السابق , تاريخ موانع الحمل الالتهابية الحوضية.النتيجة: تمت دراسة 120 مريضة من بين المرضي كانت حالات العقم الاولي بنسبة  48.3%  والعقم الثانوي بنسبة 51.7% وكان متوسط عمر مجموعة الدراسة 32 عام في كل من العقم الاولي والثانوي من اجمالي دراسة العينة 120 ثم فحص HSG كانت نسبة الطبيعي 45.8% ونسبة الغير طبيعي 54% أمراض انبوبي فالوب التي تم فحصها بواسطة HSG كانت نسبتها 46.7% وكانت النتيجة الاكثر وهي انسداد قناتي فالوب بنسبة 24.2%  وكانت نسبة انسداد الانبوب الايمن 8.8% ونسبة انسداد الانبوب الايسر 7.6% وكانت تشوهات قناتي فالوب اكثر في حالات العقم الثانوي.خلصت الدراسة إلي ان العقم الثانوي اكثر شيوعا من العقم الاولي وان تشوهات قناتي فالوب هي ايظا اكثر شيوعا في العقم الثانوي من العقم الاولي ووجود انسداد في  قناتي فالوب اكثر شيوعا في العقم، كما اظهرت الدراسة ان HSG حيوي للغاية في الكشف عن تشوهات قناة الولادة وباالتالي بجب توفير مرفق لهذه العملية الهامة خاصة التنظير الفلوري في المراكز الصحية للتقين المناسب للنساء المصابات بالعقم .